1976
DOI: 10.1172/jci108457
|View full text |Cite
|
Sign up to set email alerts
|

Disturbed islet-cell function related to endogenous gastrin release. Studies on insulin secretion and glucose tolerance in pernicious anemia.

Abstract: A B S T R A C T The insulin and gastrin response to oral glucose, intravenous glucose, or a protein-rich meal were measured in 44 nondiabetic patients with pernicious anemia (PA) and in 44 control subjects. 36 of the PApatients had hypergastrinemia, while serum gastrin concentrations in the remaining eight patients were below normal. Three hypergastrinemic PA-patients were in addition studied during an oral glucose loading with synchronous intravenous infusion of gastrin-17.During both oral and intravenous glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

1978
1978
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(27 citation statements)
references
References 41 publications
0
27
0
Order By: Relevance
“…Synthetic human gastrin-17 was used also as standard and tracer [22]. Details on assay reliability have been published previously [17,23], Antiserum 2604 binds serum gastrin components 1-IV with al most equimolar potency [14,15]. All gastrin determi nations were carried out in the same assay.…”
Section: Methodsmentioning
confidence: 99%
“…Synthetic human gastrin-17 was used also as standard and tracer [22]. Details on assay reliability have been published previously [17,23], Antiserum 2604 binds serum gastrin components 1-IV with al most equimolar potency [14,15]. All gastrin determi nations were carried out in the same assay.…”
Section: Methodsmentioning
confidence: 99%
“…This is in contrast to previous animal and retrospective studies and to human studies using exogenous gastrin in modest doses [6] or endogenous hypergastrinaemia correlating with insulin secretion [7,8]. In one animal study [5], rodents were fed a high-energy diet until they reached a morning blood glucose level >10 mmol/l.…”
Section: Discussionmentioning
confidence: 92%
“…Similarly, studies on rodents (Psammomys obesus) have shown that gastrin treatment stimulates insulin secretion, thereby reducing the blood glucose levels and increasing beta cell mass [5]. Moreover, studies in man have shown that moderate hypergastrinaemia (exogenous as well as endogenous gastrin source) also increases insulin secretion [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…It is, however, possible that a low level of expression has physiological significance. Hence, the concentration of locally released gastrin may be sufficient to affect the growth of neighboring pancreatic cells, as illustrated by the islet cell hyperplasia (35)(36)(37) and hyperinsulinemia (38) accompanying hypergastrinemia in man. In this context, the complete sulfation of pancreatic gastrin (refs.…”
Section: Discussionmentioning
confidence: 99%